Epitope Mapping of Atlantic Salmon Major Allergen by Peptide Microarray Immunoassay - Perez-Gordo, Marina; Lin, Jing; Bardina, Ludmilla; Pastor Vargas, Carlos; Barbara Cases; Vivanco Martínez, Fernando; Cuesta-Herranz, Javier; Sampson, Hugh A. (International Archives of Allergy and Immunology, 2011)
Background: IgE epitope mapping of allergens reveals important information about antigen elicitors involved in allergic reactions. The peptide-based microarray immunoassay offers an advantage of scale and parallel design over previous methods of epitope mapping. It has been used to map epitopes of some food allergens but has never been used with fish allergens. Objective: We sought to develop a peptide microarray immunoassay to map allergenic fish epitopes of two isoforms of Atlantic salmon (Salmo salar) parvalbumin, Sal s 1 beta 1 and Sal s 1 beta 2. Methods: Sera from 16 fish-allergic patients with specific IgE to salmon parvalbumin were used. Twelve healthy volunteers were used as negative controls. A library of overlapping peptides was synthesized commercially, representing the primary sequence of Sal s 1 beta 1 and Sal s 1 beta 2. Peptides were used to analyze allergen-specific IgE antibodies by immunolabeling with patient sera. Results: Three antigenic regions, not previously described, were identified in Sal s 1 beta 1. Two of them correlated with those previously reported in Gad c 1, parvalbumin from Baltic cod (Gadus callarias). No allergenic regions were found in Sal s 1 beta 2. This could be explained by crucial amino acid substitutions between isoforms. Conclusions: We have identified three antigenic regions in Sal s 1 beta 1 using a peptide microarray immunoassay. These three sequential epitopes formed a unique antigenic determinant in the three-dimensional model of the protein. In addition, we proved that isoforms from the same protein might have a different allergenic behavior. Depto. de Bioquímica y Biología Molecular Fac. de Ciencias Químicas TRUE pub Pagado por el autor